Effect of self-monitoring of blood pressure on diagnosis of hypertension during higher-risk pregnancy: the BUMP 1 randomized trial - Tucker, KL; Mort, S; Yu, L-M; Campbell, H; Rivero-Arias, O; Wilson, HM; Allen, J; Band, R; Chisholm, A; Crawford, C; Dougall, G; Engonidou, L; et al. (American Medical Association, 2022)
Importance Inadequate management of elevated blood pressure (BP) is a significant contributing factor to maternal deaths. Self-monitoring of BP in the general population has been shown to improve the diagnosis and management of hypertension; however, little is known about its use in pregnancy.